Effects of ω-3 Polyunsaturated Fatty Acids on Plasma Proteome in Rett Syndrome. (9th December 2013) - De Felice, Claudio; Cortelazzo, Alessio; Signorini, Cinzia; Guerranti, Roberto; Leoncini, Silvia; Pecorelli, Alessandra; Durand, Thierry; Galano, Jean-Marie; Oger, Camille; Zollo, Gloria; Montomoli, Barbara; Landi, Claudia; et al.
Abstract : The mechanism of action of omega-3 polyunsaturated fatty acids ( ω -3 PUFAs) is only partially known. Prior reports suggest a partial rescue of clinical symptoms and oxidative stress (OS) alterations following ω -3 PUFAs supplementation in patients with Rett syndrome (RTT), a devastating neurodevelopmental disorder with transient autistic features, affecting almost exclusively females and mainly caused by sporadic mutations in the gene encoding the methyl CpG binding protein 2 (MeCP2) protein. Here, we tested the hypothesis that ω -3 PUFAs may modify the plasma proteome profile in typical RTT patients with MECP2 mutations and classic phenotype. A total of 24 RTT girls at different clinical stages were supplemented with ω -3 PUFAs as fish oil for 12 months and compared to matched healthy controls. The expression of 16 proteins, mainly related to acute phase response (APR), was changed at the baseline in the untreated patients. Following ω -3 PUFAs supplementation, the detected APR was partially rescued, with the expression of 10 out of 16 (62%) proteins being normalized. ω -3 PUFAs have a major impact on the modulation of the APR in RTT, thus providing new insights into the role of inflammation in autistic disorders and paving the way for novel therapeutic strategies.